Vibration Analysis of Sandwich Panel Structures: A Homogenized Simulation Approach with Modal Analysis - Amir Reza Mousavi; Amir Hossein Kazemian (مجله مدل سازی در مهندسی)
Sandwich panels with diverse core materials and different types and materials are extensively employed in the industry and hold significant potential for improvement. This study focuses on a specific sandwich panel configuration consisting of aluminum face sheets and a polylactic acid (PLA) core with a honeycomb corrugated geometry. The design of this panel was accomplished and its behavior was simulated using CATIA software. The vibration characteristics of the panel were subsequently analyzed utilizing Abaqus software. Two simulation modes were employed: a fully identical simulation and a homogenized simulation. In the homogenized simulation, the honeycomb core composed of PLA with isotropic properties was replaced by an equivalently represented flat plate possessing orthotropic properties. To validate the accuracy of the software simulation, experimental modal testing was conducted on a physical sample. The obtained modal test results were subjected to analysis using N-modal analysis software and then compared with the analytical simulation results. Furthermore, the simulation results were compared with and without considering the adhesive connections, revealing minimal influence of the adhesive connections  (less than 1.1%) on mode shapes and natural frequencies.The simulation results and modal analysis indicate an error coefficient of less than 7%. The presented homogenization technique can be effectively employed to streamline the simulation process, reduce time requirements, and simplify the complexity of the investigated issues..